Physical Education and faces of sports - Marcelo da Silva Villas Bôas; Francisco Cock Fontanella; Vanildo Rodrigues Pereira (Revista da Educação Física)
The aim of the present review study was to analyze sports pros and cons, based on topics from national and international literature on Physical Education. It was possible to identify and discuss the opposite trends and verify the presence of ideological motivations which demonstrate the radicalization of both faces: the pros and the cons. Some moderate findings lead to the belief that it is possible to use sports both in school and out of school since childhood to promote benefits to personal balance and social life and give good quality to life.